Improvement Nutrient Digestibility and Production Performance of Cattle Through Restricted Amino Acid and Organic Minerals Addition on Fermented Palm Oil Waste-Based Feed - Kusuma Adhianto; Muhtarudin muhtarudin; Liman Liman; Agus Haryanto (Buletin Peternakan, 2018)
The objective of this research was to evaluate the effect of branched-chain amino acid and organic mineral addition on fermented palm oil waste based-feed to the nutrients digestibility and cattle performance. The research was done using nine Ongole crossbred cattle by applying randomized block design with three treatments and three replications. The first treatment (R0) was fermented palm oil waste-based feed; and the second treatment (R1) was R0 with 13% cassava leaves addition; and the third treatment (R2) was R1 with organic minerals (40 ppm Zn; 10 ppm Cu; 0.1 ppm Se; and 0.3 ppm Cr) addition. The result showed that R2 gave a significant effect (P<0.05) on crude protein, crude fiber, and ether extract digestibility, but showed no significant effect on dry matter and organic matter digestibility and cattle production parameters. The research concluded that fermented palm oil waste-based feed with 13% cassava leaves and organic minerals addition gave the best result based on the digestibility and cattle production parameters.